Feasibility of therapeutic plasma exchange-based combination therapy in the treatment of acquired hemophilia A: A retrospective 6 case series. Issue 29 (23rd July 2021) - Wang, Lin-Yue; Shen, Yan; Zeng, Han-Qing; Zhang, Ying; Lou, Shi-Feng; Deng, Jian-Chuan; Luo, Yun
Abstract : Abstract: Poor availability and a lack of affordability of bypassing agents (recombinant activated factor VII and activated prothrombin complex concentrate) in west China prompted us to investigate an alternative cost-effective combination therapy. We aimed to explore the feasibility of therapeutic plasma exchange (TPE)-based combination therapy in the treatment of acquired hemophilia A (AHA). We retrospectively investigated the clinical features of AHA in 6 patients who were treated with a combination of TPE, corticosteroids, and rituximab in our department for 9 years between January, 2011 and December, 2019. We examined 1 male and 5 female patients. The median age at diagnosis of AHA was 51 years (18–66 years). In all patients, FVIII activity levels were low (median: 1.5%; 1–3%), FVIII inhibitor titers were high (median: 24.5 BU/mL; 13.2–48.6 BU/mL), and activated partial thromboplastin time was markedly prolonged (median: 99.4 s; 60.9–110.1 s). They underwent 2 to 8 cycles of plasma exchange and were given varying combinations of dexamethasone, methylprednisolone, prednisone, and rituximab. After TPE bleeding gradually stopped, and activated partial thromboplastin time decreased. After 3 months of treatment, FVIII inhibitors completely disappeared. TPE when combined with corticosteroids and rituximab, as adjunctive immunosuppressive agents, may be an effective and reliable treatment for AHA. When there is no alternative, intensive first-line treatment including TPE may be lifesaving.